“It Hits the Spot”: The Impact of a Professional Development Program on English Teacher Wellbeing in Underdeveloped Regions - Wang, Xiaojing; Chen, Zehang (Frontiers in Psychology, 2022)
In the poor and remote areas, teachers frequently encounter serious ongoing challenges and experience teacher exhaustion, due to the uneven distribution in resource supply, low salaries, and a shortage in academic support. How to maintain teachers’ professional wellbeing in the unfavourable teaching environment has become a major challenge. The current study intends to explore teachers’ professional wellbeing in the context of a five-month professional development programme designed for teachers in deep poverty areas of China. This study adopted the method of narrative enquiry and collected diaries written before and after the programme from 46 primary English teachers. Based on the manually analysed data, it is found that teachers’ overall wellbeing at work was enhanced in terms of their professional meaning, engagement and achievement. Systematic analysis of the diaries helped to better understand how the programme exerted such effect on teachers’ learning experiences and their wellbeing.